(untitled) (REMUNOM, 2026)
Population growth triggers a series of events, among which the increase in food production stands out as a way to meet societal demand. It is therefore necessary to consider the role of family farmers in the development of this food chain, and also in strengthening the distribution of food to surrounding communities. Furthermore, it is necessary to consider the role of these agroecological rural producers in keeping people in the area, and their production can be considered more sustainable and healthy than that used by conventional agricultural activities, which often use pesticides. The objective of this research is to investigate the landscape of public policy incentives in Brazil that strengthen family farming for the healthy food development of the population. A qualitative-quantitative literature review was conducted, using the SciELO platform and the CAPES Periodicals database as research instruments. To this end, an analytical matrix was constructed to better delineate the research, in order to cross-reference the research findings with the purpose of quantifying and categorizing them. The results indicated that federal government policies already exist to incentivize family farming, and that these policies bring benefits to product marketing, income generation, and social participation. However, small farmers still face difficulties participating in these programs due to bureaucracy, the amount of paperwork, and the necessary formalization processes. The need for training for small rural farmers is considered, as this activity, when carried out using agroecological principles, can promote food security and social participation for these individuals.